An updated checklist of marine gastropods of the Persian Gulf and Gulf of Oman - Amini-Yekta, Fatemeh; Dekker, Henk (Zootaxa, 2021)
Here we review and evaluate the marine gastropods of the Persian Gulf and Gulf of Oman based on published accounts. A total of 850 species belonging to 129 families have records in the Persian Gulf (585) and Gulf of Oman (648), of which 383 species occurred in both regions. We updated the taxonomy and deleted records with dubious identifications. The resultant checklist documents the currently known diversity of marine gastropods from the Persian Gulf and Gulf of Oman and provides a foundation for future studies of the biodiversity of these areas.